2012
DOI: 10.1001/archsurg.2011.1404
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Hepatic Resections in Obese Veterans

Abstract: To determine the effects of body mass index (BMI; calculated as weight in kilograms divided by height in meters squared) on outcomes after liver resection performed at Veterans Affairs medical centers. Design, Setting, and Patients: We queried the Veterans Affairs Surgical Quality Improvement Program database for liver resections (2005-2008) and grouped the patients into 5 BMI categories: normal weight (BMI 18.5-24.9), overweight (BMI 25.0-29.9), obese class 1 (BMI 30.0-34.9), obese class 2 (BMI 35.0-39.9), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This may reflect the fact that obese people have good nutritional and physiological reserves and show enhanced inflammatory response to injury, which may counteract comorbidity and mortality among obese patients undergoing hepatectomy [ 11 , 38 ]. On the other hand, some authors have reported that obesity worsens the prognosis of HCC patients [ 9 , 10 ]. Further studies are needed to clarify these differences before definitive conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect the fact that obese people have good nutritional and physiological reserves and show enhanced inflammatory response to injury, which may counteract comorbidity and mortality among obese patients undergoing hepatectomy [ 11 , 38 ]. On the other hand, some authors have reported that obesity worsens the prognosis of HCC patients [ 9 , 10 ]. Further studies are needed to clarify these differences before definitive conclusions can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that obesity is not an independent risk factor in laparoscopic colorectal surgery [28–32]. However, Saunders et al [33] showed that a high level of obesity (BMI ≥ 40.0) was an independent risk factor for higher transfusion rates and increased mortality. They suggested that this information should be considered when discussing alternative therapies (e.g., ablation) in patients with extreme obesity and malignant liver neoplasms.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that obese patients as well as overweight patients have more co-morbidities, such as cardiovascular disease and diabetes mellitus[3], [11], [12], [25]. In addition, two studies with large samples earlier indicated that obese and overweight patients did increase workload for surgeons by adding operating time or length of hospital stays[2], [26].…”
Section: Discussionmentioning
confidence: 99%
“…The accompanying chronic liver disease in HBV-related HCC patients may cause more severe complications than in other patients[30]. Second, the absence of unified standards in reported complications hampered proper evaluation of the surgery results in several large-sample studies[2], [8], [11], [25][27]. Thirdly, for liver resection in HCC patients, most cohorts[12][14] had a small sample of patients and the statistical power was limited.…”
Section: Discussionmentioning
confidence: 99%